Pengaruh Audit Internal dan Pengendalian Internal terhadap Penerapan Good Corporate Governance: Studi pada Bank Tabungan Negara Kantor Cabang Jambi - Nadia Putri; Netty Herawaty; Rahayu Rahayu (OPTIMAL Jurnal Ekonomi dan Manajemen, 2025)
The purpose of this study is to investigate how internal audit and control affect the Bank Tabungan Negara Jambi Branch Office’s application of sound corporate governance. This study employs a quantitative descriptive method research strategy. Saturated sampling is utilized to decide the responder determination procedure, meaning that all 45 participants in the research are employed as a sample. By distributing questionnaires, data is gathered in the form of primary data. With the use of smartPLS software version 4, the data analysis technique employed the Partial Least Square (PLS) approach in the Structural Equation Model (SEM). The findings demonstrated that the application of sound corporate governance was impacted by internal audit. The degree to which sound corporate governance principles—such as accountability, responsibility, independence, openness, and fairness—are used in the workplace improves with the effectiveness of internal auditing. In a similar vein, good corporate governance is influenced by the internal control variable. Strong internal controls reduce the possibility of fraud, abuse of power, and managerial mistakes, allowing for the consistently application of good corporate governance.